IMPLEMENTATION OF GEOGRAPHY LEARNING BY TEACHERS IN FORMING CHARACTER ENVIRONMENTALLY CONSCIOUS AT SMAN 1 PASANGKAYU - Della; Nisa , Zumrotin (LPPM Universitas Tadulako, 2021)
This research aims to determine the implementation of geography learning by teachers in forming environmentally-minded characters at SMAN 1 Pasangkayu. This research is a type of quantitative research with a descriptive approach. The population in this study was all students in class XI IPS at SMAN 1 Pasangkayu, a total of 41 students. Data collection techniques were carried out using questionnaires distributed directly to students, observation, interviews, and documentation. The data analysis technique used is a descriptive statistical analysis using a percentage formula. The results of the research show that the implementation of geography learning in the classroom has a total of all indicators, namely 17 assessment intervals in the (sufficient) category and research on the implementation of geography learning by teachers in forming environmentally sound character at SMAN 1 Pasangkayu has a total percentage of 67.24%. overall is in the (good) category, the total percentage is obtained from the four indicators of environmentally sound character, namely: (1) Using resources economically and implementing conservation, (2) Reusing and recycling used materials, (3) Utilizing renewable resources, (4) Controlling population density. So it can be concluded that the implementation of geography learning by teachers in forming environmentally-minded character at SMAN 1 Pasangkayu is in the good category.